Study on the heat and mass transfer in AGMD module with latent heat recovery. Issue 33 (14th July 2016) - Geng, Hongxin; Lin, Long; Li, Pingli; Zhang, Chunyao; Chang, Heying
Abstract: A novel air gap membrane distillation (AGMD) module for desalination with latent heat recovery which consisted of parallel hollow fiber membranes and heat exchange hollow fibers was successfully developed. The temperature profiles of AGMD module designed with latent heat recovery along the radial direction and mass transfer coefficient across membrane ( C m ), Knudsen diffusion coefficient across membrane ( C Km ), molecular diffusion coefficient across membrane ( C Mm ), and molecular diffusion coefficient in air gap ( C Ma ) were obtained by establishing a heat and mass transfer model. The permeate flux ( J D ) was highly sensitive to the hot feed inlet temperature, T hi . The maximum value of J D could reach 15.5 kg/m 2 h for module 1 and 20.2 kg/m 2 h for module 2 at T hi = 90°C and T ci = 30°C. The value of actual mass transfer coefficient across the membrane was in close to the value of Knudsen diffusion coefficient across the membrane, especially at high hot feed brine temperature. The membrane wall was the main resistance for mass transfer and contributed 60–70% to the total mass transfer resistance. The heat transfer across the heat exchange hollow fiber was the main heat transfer resistance and the heat transfer across the heat exchange hollow fibers was only around 3, 238.1 W/m 2 °C. The temperature polarization coefficient was introduced to measure the actual driving force.